Monozygotic Twins Suffering From Sodium Taurocholate Cotransporting Polypeptide Deficiency: A Case Report - Tan, Hui-Jun; Deng, Mei; Qiu, Jian-Wu; Wu, Jun-Feng; Song, Yuan-Zong (Frontiers in Pediatrics, 2018)
Sodium taurocholate cotransporting polypeptide (NTCP) is a carrier protein encoded by the human SLC10A1 gene, acting as the principal transporter of conjugated bile salts from the plasma into hepatocytes. Although NTCP was cloned as early as in 1994 and its function has been studied extensively, clinical description of NTCP deficiency remains rather limited thus far. The patients in this paper were 2 female monozygotic twins, who were referred to our hospital at the age 2 years with the complaint of persistently-raised total bile acids (TBA) for 21 months. At age 3 months, they were both diagnosed to have cholestatic liver disease due to raised serum TBA and direct bilirubin (DBIL) with the fraction >20% of the elevated total bilirubin (TBIL). Thereafter, their jaundice subsided and the DBIL levels recovered gradually, while serum TBA remained raised persistently. In view of their refractory hypercholanemia but negative symptoms and signs, SLC10A1 genetic analysis were performed for all family members to evaluate the possibility of NTCP deficiency. As a result, the twins were both homozygotes, while the parents, carriers, of the reportedly pathogenic variant c.800C>T (p.Ser267Phe). These findings suggested that NTCP deficiency may be a unique genetic factor causing transient cholestasis in early infancy as well as persistent hypercholanemia in pediatric patients.